THE REALITY OF THE IRAQI ECONOMY AND ITS STRUCTURAL CHANGES - Zahraa Kareem Sabri (Scholar Express Journals, 2025)
Economic indicators declined during the period (1990-2003) as a result of the continuous wars from the Iran-Iraq War to the Gulf War, in addition to international sanctions. In an attempt to revive an economy that witnessed structural imbalances in the economic structure, the latest of which was the issue of destabilizing dependence on the oil sector after the United Nations supervised and restricted oil revenues, one of the most important urgent issues for Iraqi economic decision-makers in order to diversify sources of local income. Here, the researcher seeks to analyze the economic variables represented by economic growth. The Gross Domestic Product (GDP) of any country reflects the total output of various goods and services by citizens and foreigners within the country during a specific period of time. Analyzing the contribution of the main sectors to the formation of the GDP represents a very important indicator in the economy, as it shows the contribution of each sector to the output, its role in exploiting available resources, operating means of production, and the extent of its contribution to economic growth.
Keywords: reality; Iraqi economy; structural changes